As operações com números naturais e alunos em dificuldades do 8º ano do Ensino Fundamental - Soares, Natália Coelho (2012)
This research aimed to investigate whether and how eighth-grade middle school students who have difficulty in solving mathematical operations with natural numbers deepen their knowledge in this field when they have the opportunity to work with technological tools that are not frequently used in classroom. Data collection was based on twelve semi-structured interviews, which were done according to André (2008) concept of study of case. The students conceptions about solving mathematical operations with natural numbers were analyzed based mainly on the APOS theory. It was concluded that by introducing technological tools that are not frequently used in classroom, such as abacus and printing calculator, the students were allowed to deepen their knowledge about natural numbers and, consequently, reframe their conceptions about it